A comprehensive review of supercapacitors: Properties, electrodes, electrolytes and thermal management systems based on phase change materials. (15th December 2022) - He, Xiyue; Zhang, Xuelai
Abstract: As an energy conversion and storage system, supercapacitors have received extensive attention due to their larger specific capacity, higher energy density, and longer cycle life. It is one of the key new energy storage products developed in the 21st century. However, the performance of supercapacitors is limited by its electrode materials and electrolytes. At the same time, with the application of supercapacitors in electric vehicles and renewable energy systems, thermal safety issues have become increasingly prominent. A proper thermal management system can control the temperature of the supercapacitor module during charging and discharging, which is crucial to ensure the performance and safety of the energy storage system. Among various cooling technologies, phase change material (PCM) has been widely used due to its simple structure, good cooling effect, and no additional energy consumption. In this paper, the principle, characteristics, electrode material types, electrolyte types and research progress of PCM materials in supercapacitor thermal management systems are reviewed. Finally, an overview of the current application of supercapacitors is pointed out, and the future development direction is prospected.